Problematic of Implementing The Independent Curriculum - Putri, Elya Shafiira Setyawan; Markhamah, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study seeks to address challenges encountered in Indonesian language teaching under the Independent Curriculum at the Stage E (class X) level at SMA Negeri 1 Polanharjo. Specifically, it examines teacher readiness, the extent of school support, facilitating and hindering factors in curriculum implementation, and potential strategies to overcome identified obstacles. Methodology: Adopting a descriptive qualitative design, researchers collected written data from recorded, semi‐structured interviews with Indonesian language teachers responsible for Stage E instruction. Interview recordings were meticulously transcribed and then analyzed to map out recurring themes related to preparedness, institutional backing, enablers, barriers, and proposed remedial steps. Results: Analysis revealed a spectrum of teacher readiness—ranging from enthusiastic early adopters to those uncertain about curriculum shifts—often correlated with the level of in‐school professional development provided. School support varied: some departments offered regular workshops and resource materials, while others lacked clear guidance. Key supporting factors included strong leadership commitment and peer collaboration; major obstacles centered on insufficient training time, limited instructional resources, and ambiguous assessment guidelines. Teachers proposed concrete steps—such as targeted in‐service training sessions, development of clear teaching modules, and establishment of a teacher‐mentoring network—to bridge these gaps. Applications/Originality/Value: y systematically documenting real‐world readiness levels, support structures, and both facilitators and inhibitors of curriculum change, this study offers actionable insights for school administrators and district policymakers. Its findings can inform the design of focused professional‐development programs, allocation of teaching resources, and creation of collaborative support networks, thereby enhancing the fidelity and effectiveness of Independent Curriculum implementation in Indonesian language classrooms.